The role of HLA-DRB1 alleles on susceptibility and outcome of a Portuguese Multiple Sclerosis population. - Silva, A; Pereira, C; Bettencourt, A; Carvalho, C; Couto, A; Leite, M; Marta, M; Freijo, M; Costa, P; Mendonça, D; Monteiro, L; Armas, J; et al. (2007)
BACKGROUND: The association between susceptibility to multiple sclerosis (MS) and HLA-DRB1*15 has been reported in various European populations. OBJECTIVE: To investigate the relationship between MS, HLA-DRB1*15 and other DRB1 alleles in a Portuguese population and their association with clinical course of MS. METHODS: The HLA-DRB1 alleles were analyzed by PCR-SSP in 248 MS patients and 282 healthy controls. In order to relate HLA-DRB1 alleles to disease aggressiveness, patients with relapsing remitting MS and secondary progressive MS were subdivided into 3 groups: 'benign' MS patients who maintain an Extended Disability Status Scale (EDSS) score of <or=3 10="" after="" at="" disease="" edss="" least="" ms="" non-benign="" onset;="" patients="" with="" years="">3 after the same period and 'aggressive' MS those with EDSS>or=6 within 15 years of disease onset. RESULTS: As expected, a higher frequency of HLA-DRB1*15 was found in MS patients (29.8% vs 19.9%, odds ratio (OR)=1.72, 95% CI=1.15-2.56, p=0.008). The HLA-DRB1*03 allele was positively associated with MS in the overall patient population (22.6% vs 15.6%, OR=1.58, 95% CI=1.02-2.45). Concerning disease aggressiveness, HLA-DRB1*15 occurred more frequently in the group with benign disease (42.6% vs 19.9%, OR=2.99, 95% CI=1.56-5.72) and in the group with non-benign disease (34.1% vs 19.9%, OR=2.09, 95% CI=1.05-4.16) compared with controls. When time to reach an EDSS=3 or EDSS=6 was considered as end point, HLA-DRB1*15 negative patients were found to have a worse prognosis. CONCLUSIONS: In this population of Portuguese MS patients, the HLA-DRB1*15 allele is established as a genetic marker for susceptibility to MS and is also associated with a better outcome.</or=3>